Creating the Conditions to Create: An Anti-Oppressive Lens on the Post-Pandemic Music Scene - Howell, Carlie (Critical Studies in Improvisation / Études critiques en improvisation, 2021)
As a professional bassist who identifies as female and queer, I have my share of horror stories about experiences in the music industry. But I also have a solid peer group that is actively working to improve things, and with whom I have an ongoing dialogue. Specifically, in the last year, we started to observe the radical behavioural changes we've made as a society in response to the COVID-19 pandemic, and how these protocols could be viewed with an anti-oppressive lens. I started to think about my values as an improvising musician, and how they provide an analogy and a framework for broader social interaction. I used the writing of this article as an opportunity to speak with some of my musical peers about their individual experiences and their ideas for creating safer spaces. We talked about the skills we had as improvisers, and how the pandemic could be a pivot point in creating a safer, more authentically inclusive music scene for women, trans, and gender queer people. This piece reflects those conversations and offers practical considerations and theoretical frameworks that are relevant to individual improvisers and ensembles, as well as promoters, curators, and venues.